1989
DOI: 10.1021/ja00197a056
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic facial selectivity in nucleophilic displacements at tetracoordinate phosphorus: kinetics and stereochemistry in the reaction of sodium ethoxide with O,S-dimethyl phenylphosphonothioate

Abstract: The reaction of ethoxide ion with 0,S-dimethyl phenylphosphonothioate (la) proceeds with competitive displacements of the methylthio and methoxy ligands. Each displacement occurs with complete inversion of configuration. The two products, ethyl methyl phenylphosphonate (2ab) and O-ethyl S'-methyl phenylphosphonothioate (lb), respectively, react further with ethoxide ion to form diethyl phenylphosphonate (2bb). Displacement of the ethoxy ligand on 2ab or lb, which leads to racemization, competes with formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 0 publications
5
49
1
Order By: Relevance
“…Thus, enantiopure (R)-1a , (S)-1a was found to have potential as a solvating agent for the determination of the ee of chiral compounds by 1 H NMR spectroscopy. Four research groups have reported the enantioseparation of racemic 1a by using brucine ( 3 ) as a resolving agent through almost the same procedure . However, the reproducibility of the method was very poor, although we tried the enantioseparation of racemic 1a with 3 with an all‐out effort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, enantiopure (R)-1a , (S)-1a was found to have potential as a solvating agent for the determination of the ee of chiral compounds by 1 H NMR spectroscopy. Four research groups have reported the enantioseparation of racemic 1a by using brucine ( 3 ) as a resolving agent through almost the same procedure . However, the reproducibility of the method was very poor, although we tried the enantioseparation of racemic 1a with 3 with an all‐out effort.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reproducibility of the method was very poor, although we tried the enantioseparation of racemic 1a with 3 with an all‐out effort. Moreover, the research groups have guaranteed the optical purities of the enantiomers of 1a only on the basis of their specific rotations or those of the salts of 1a with dicyclohexylamine, and opposite signs have also been reported for ( R )‐ 1a · dicyclohexylamine and ( S )‐ 1a · dicyclohexylamine. On the other hand, Lewis et al have established a method for the enantioseparation of racemic 1a with enantiopure 1‐phenylethylamine .…”
Section: Resultsmentioning
confidence: 99%
“…In this way, a pentavalent trigonal bipyramidal intermediate is formed, where the nucleophile and the leaving group are located on the apical positions (see Figure 6). [105][106][107][108] In OPCs with more than a potential leaving group, the intermediate structure influences which group will be replaced, determining the product stereochemistry. In OPCs, it is common a competition between a alcoxy and a thioalkyl leaving group, the former being more electronegative and the latter being more polarizable, less basic and, therefore, a better leaving group.…”
Section: Mechanism Of Action Of Opcsmentioning
confidence: 99%
“…However, the possibility of occurrence of pseudorotations around the phosphorus atom and the possible existence of steric hindrances may result in a less electronegative group occupying an apical position in the intermediate, so becoming the preferable leaving group. 106,110,111 So, breaking of a P-O or a P-S bond will be the result of a competition between the apicophilicity of the alcoxy group, kinetically favored, and the better stability as leaving group of the thioalkyl group, thermodynamically favored. 106,108,112 OPCs cause several deleterious effects in the organism, since ACh accumulation results in an excessive stimulation of nicotinic and muscarinic receptors in both central and peripheral nervous systems.…”
Section: Mechanism Of Action Of Opcsmentioning
confidence: 99%
See 1 more Smart Citation